Children’s participation in social work research. A secondary data analysis of an umbrella review of children’s participation in child welfare - McCafferty, Paul; Mercado García, Esther (The British journal of social work)
Abstract The real participation of children and young people (C&YP) in decisions affecting their lives and rights gained traction with the 1989 adoption of the UN Convention on the Rights of the Child, particularly Article 12, which asserts children's rights to express their views and have them respected. This principle recognizes children as active societal agents, not just passive subjects. This study, based on these principles, analyses secondary data from a prior umbrella review by the authors, focusing on children’s involvement in research processes. Using an adapted version of Shier's (2019) model, the study highlights a worrying dependence on traditional, adult-centred research methods that largely overlook young participants' perspectives. Although some creative, child-friendly methods are used, they are sporadic, revealing a gap in engaging younger children effectively. The study also finds that children's participation is often tokenistic rather than genuinely collaborative. These findings emphasize the need for more inclusive and innovative research practices to empower C&YP as co-creators of knowledge. Bridging these gaps is essential for promoting a more child-centred, equitable approach in research, which values every child's contribution and fosters a more inclusive society. The recognition of children and young people's (C&YP) active involvement in decision-making, particularly in matters affecting their lives, gained prominence with the 1989 adoption of the United Nations Convention on the Rights of the Child. Central to this is Article 12, which emphasizes the importance of not only hearing children's views but giving them due weight. This study, rooted in these principles, analyses secondary data to examine the extent of C&YP's participation in research processes. The findings reveal a concerning reliance on adult-centred methodologies that overlook the unique perspectives of younger participants, highlighting a significant gap in inclusive, child-friendly research practices. Moreover, the study exposes the tokenistic nature of children's roles in decision-making within research, underscoring the need for more innovative and collaborative approaches that empower children as co-creators of knowledge. These insights pave the way for a more equitable, child-centred research landscape, ultimately contributing to a more inclusive society.